ZAKAH MANAGEMENT IN SAUDI ARABIA, SUDAN AND INDONESIA - Uswatun Hasanah (Universitas Trisakti, 2014)
According to Islamic law, zakah is one of the pillars of Islam that must be performed by every Muslim, wherever they are. Zakah is essentially part of assets that must be expended by any Muslim, under the command of Allah for the benefit of others according to the levels specified by Him. Those expenditures are mandatory for any Muslim as a sign of gratitude for the blessings and gift of Allah, as an attempt to draw closer to Him, and also as a means to clean the property and individuality as a human. In addition, the purpose of zakah (Islamic tithe) obligation is to achieve social justice and welfare. Therefore, amil (zakah collector) as zakah manager shall always try hard and ascertain that the zakah he manages can improve the welfare of the community. For that reason the effectiveness or ineffectiveness of zakah to the improvement of the community is largely dependent on the amil. But in reality, there are still some countries whose zakah institution has not been functioning properly such as Indonesia. Therefore, Indonesia must take lesson from the countries that have succeeded in managing zakah properly, such as Sudan and Saudi Arabia.Keywords: zakat; amil.